Problems of legal regulation of thin capitalization in Ukraine - Pyroha, Serhii (Problems of legality, 2024)
The proliferation of multinational companies is lengthening global value chains, and the development of the digital economy is giving them even more opportunities to shift profits. Intra-group loans are often used to shift profits to a jurisdiction with low tax rates to minimize overall tax liability. In order to combat the illegal transfer of profits, most countries introduce thin capitalization rules. Ukraine joined the BEPS plan, action 4 of which summarized the best practices for regulating debt obligations to non-residents. Most countries limit the total amount of loans, interest payments on which are deducted from the corporate tax base. The Tax Code of Ukraine establishes a double tax barrier - it limits both the amount of debt and the share of profit before deduction. However, the established barriers not only do not prevent profit shifting, but encourage the widespread use of this method to reduce tax liabilities due to profit shifting. The main drawback of thin capitalization rules is that allowed excessive amounts of loans from non-residents do not oblige the borrower to improve the financial results of the enterprise. Instead, they provide an opportunity to reduce the corporate tax base by 30% indefinitely and move them to jurisdictions with low tax rates. The method of regulation provided for by the Tax Code of Ukraine can be considered as an incentive for the misuse of State budget funds. In order to eliminate these shortcomings, it is proposed to significantly reduce both barriers and to oblige the borrower to ensure the effective use of loans to stimulate the socio-economic development of the country, i.e. to deduct interest from taxable profit only if there is an actual increase in the produced added value, the introduction of new products and/or processes. Existing shortcomings in the legal regulation of debt obligations prevent legal resolution of the case in court. New criteria for identification of the resident with regard to individuals and legal entities and the beneficial owner of income have been proposed.